Tasawwuf literature in the context of Islamic education: a bibliometric study - Ahmad Handhalas Shamsuddin,; Che Zarrina Sa’ari,; Mohd Syukri Zainal Abidin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Tasawwuf or Islamic mysticism holds a significant place in Islamic scholarship and spirituality. Its literature has contributed profoundly to the development of Islamic thought, ethics, and education. However, despite the undeniable influence of Tasawwuf literature on Islamic education, a comprehensive bibliometric analysis of this body of work remains lacking. To address this gap, it is crucial to explore and quantify the scholarly output, dissemination, and impact of Tasawwuf -related research within the context of Islamic education. In this bibliometric study utilizes a systematic approach to analyze a vast corpus of academic literature. We begin by collecting relevant research articles papers from reputable academic databases and repositories. Subsequently, we employ bibliometric techniques, including citation analysis, co-authorship networks, and keyword mapping, to assess the trends, patterns, and connections within Tasawwuf literature in the context of Islamic education. The findings of this study are expected to reveal the most influential works, prolific authors, and leading academic institutions in the field of Tasawwuf literature within Islamic education. Additionally, the analysis will identify emerging research themes and gaps in the existing literature. Insights into the evolution of Tasawwuf scholarship and its intersections with Islamic education will be provided. Conclusion, this bibliometric study will offer valuable insights into the scholarly contributions of Tasawwuf literature to the field of Islamic education. By mapping the intellectual network and identifying influential works and authors, it will facilitate future research directions and promote a greater understanding of the historical and contemporary significance of Tasawwuf within Islamic education.